The Effect of Strategic Learning, Motivation and Quality of Student Officers Against Military Capability Effectiveness - Daniel Setiawan; R. Madhakomala; Ucu Cahyana (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
The purpose of this study was to determine the effect of motivation study strategic and quality of Student Officers on the effectiveness ability military participant to educate School Naval Staff and Command (Seskoal). This research is associative quantitative research; the research was carried out using a survey method with the technique of analysis is the data used to answer hypothesis with the technique of Structural Equation Modeling. The sample in this study was 138 respondents consisting of Student Officers, Lecturers, Educators, Heads of Work Units, and Officials Seskoal selected using random sampling with d = 0.05 with a level of 95% confidence. The data analysis technique used SEM PLS software. Research is focused on aspects of motivation study strategic and quality of Student Officers on effectiveness ability military. The results of the analysis conclude that (1) there is a direct influence of motivation study on effectiveness ability military, ( 2 ) there is a direct influence on the quality of officers student on effectiveness ability military, ( 3 ) there is direct influence by together motivation learning and officer quality students on effectiveness ability military.